Highlights of Archaeological Studies in Jaffna Peninsula since 2010 - Pushparatnam, P. (JUICE- 2012 University of Jaffna, 2012)
Among the Historical significant regions in Sri Lanka, Jaffna Peninsula is very unique. The Jaffna Peninsula is referred to as “Nagadipa(m)”, in Pali and Nakanadu in Tamil literary works from sixth century B.C. to 13th century A.D. However the early History of Jaffna was not distinct and clear when compared with other Historical regions in Sri Lanka as evidenced by the literary works of Historical value. As such Archaeological evidences play an important part in tracing the ancient and medieval History of Jaffna Peninsula. In 1970, Archaeologists from the University of Pennsylvania conducted scientific Archaeological excavation at Kantarodai in Jaffna Peninsula, for the first time. As a result, evidences are discovered including human migration from South India to Kantarodai in Jaffna Peninsula took place during the Megalithic or Iron Age culture period, about 2500 years ago. Further, similar evidences have been discovered at various places in Jaffna like Anaikkoddai, Karainakar, Mannithalai, and Caddi. In 2010 and 2011, the Department of Archaeology and University of Jaffna together conducted excavations and explorations at Jaffna Fort and Kantarodai and have discovered various different artifacts and evidences belonging to different periods. The evidences discovered in Jaffna reveal some important aspects about the early people, their culture and their ties with people of other regions of Sri Lanka and with the people of foreign centuries. The objective of this research is to study the artifacts and evidences in detail and to document them and to make people know these Archaeological findings.